Link Layer Time-Varying Model for IEEE 802.15.4 Radio in Industrial Environment - Wan Yadong; Duan Shihong (International Journal of Distributed Sensor Networks)
IEEE 802.15.4 PHY has been widely used in wireless sensor networks. In-depth investigations on the link layer characteristics are important for WSN protocol design. In industrial environments, link reliability is vulnerable to various interferences; therefore, many schemes have been employed for reliability improvements such as multichannel access, frequency hopping, and multipath routing, which put forward the demand on link reliability models. Previous researches mainly focus on distance fading and irregularity of link reliability; however, little work analyses the temporal and frequency variations of the link reliability. The paper proposed a link layer statistical model (LTM) for time-varying of 16 channels based on packet drop rate (PDR) data collected from typical industrial environments. LTM descript packet drop intervals, PDR variation over times, PDR variation between different channels, link level switching probability and interference distribution. And also, a discussion of the influence of IEEE 802.15.4e MAC protocol simulation showed that LTM is closer to the realistic result. This paper provides a new method to model link reliability in industrial environment and is useful to the design of frequency diversity and upper layer protocols.